MANAGEMENT OF CHANGES IN THE IMPLEMENTATION OF THE COMPANY'S STRATEGY (Development Service Industry Management, 2024)
Strategic thinking is critical to surviving and thriving in today's volatile business environment. Strategic management helps managers identify new opportunities and find new ways to create and sustain competitive advantages to deliver value to consumers. The importance of change management research in strategy implementation is determined by the need to generalize theoretical aspects and form practical recommendations regarding a specific set and sequence of implementation actions. In scientific publications, it is noted that targeted and coordinated efforts to translate the developed strategy into specific changes are an integral component of strategic management. The purpose of the article is to study the theoretical and practical aspects of change management in the implementation of the company's development strategy in conditions of instability and uncertainty. A generalization of the existing views on the content of the strategy implementation process in the enterprise's practice has been carried out. Strategic changes, change implementation organization, change management and strategy adjustment are defined as components of the strategy implementation system. We offer our own view on the stages of strategy implementation and their content. The tasks that must be solved by change management at the stage of strategy implementation are defined. Indicated. that the system of strategic changes should provide the basic requirement in the conditions of war and a high level of instability - the viability of the organization and the possibility of development. It is proposed to classify the changes in accordance with the criterion of the possibility to ensure the implementation of the strategy. The article proposes a methodology for assessing strategic changes based on the criteria of strategic relevance, benefits, risks, and resources.
Keywords: strategic management; strategy implementation; strategic changes; change management